Building an atlas of knowledge for invasion biology and beyond! 2nd enKORE-INAS Workshop - Bernard-Verdier, Maud; Heger, Tina; Mietchen, Daniel; Musseau, Camille; Brinner, Marc; Hillig, Alexander; Kraker, Peter; Lokatis, Sophie; Nunes, Ana Luisa; Scheidweiler, Nils; Stocker, Markus; Vial, Roxane; et al. (Research Ideas and Outcomes, 2023)
With the exponential increase in scientific publications, new conceptual and technological tools are needed to help scientists, students, managers and policy-makers to navigate and digest current scientific knowledge. Hi Knowledge is an initiative to synthesise and visualise scientific knowledge, with an initial focus on invasion biology that is currently expanding to include urban ecology, restoration ecology and freshwater ecology. In a workshop on 5-6 June 2023 in Berlin, Germany, we discussed and tested a collection of new open tools related to this initiative in order to publish, curate, explore and synthesise concepts and results in ecology. Three main themes were discussed during in-person breakout group sessions: (1) building and using open tools for knowledge curation, exploration and synthesis; (2) making open knowledge searchable and machine friendly by improving modelling and annotation of scientific knowledge; and (3) extending beyond the field of invasion biology. We report on the discussions of all twelve sessions pertaining to these themes. A main underlying goal of our workshop was to build a community of scientists involved in openly co-designing and using these tools. Overall, the participants were enthusiastic about the usefulness of these tools and discussions gravitated around improving them and finding strategies to scale-up participation by the community. Follow-up user tests and publications are planned for individual tools and topics.